A Conceptual Comparison of Hydraulic and Electric Actuation Systems for a Generic Fighter Aircraft - Alessandro Dell’Amico; Christopher Reichenwallner (Aerospace)
This paper presents a methodology for evaluating different flight control actuation system architectures in the early conceptual design phase. In particular, this paper shows how hydraulic and electric actuators can be modeled even if very little is known about the aircraft design or requirements while still including the most dominant static and dynamic characteristics. Singular Value Decomposition is used to estimate model parameters and actuator characteristics from industrial data. This is a quick way to estimate what is needed with little input. The purpose of the models is to predict the power consumption, cooling needs, weight, and size. This is performed by integrating the actuator models in a dynamic simulation framework that also includes a flight simulator and surrounding systems. The results from subsystem studies support the aircraft design process, where actuator characteristics affect the engine performance and aircraft sizing. The methodology is applied to a generic fighter by comparing hydraulic and electric actuation system architectures. Besides providing a generic approach to the actuator modeling, the parameters that affect both the static and dynamic characteristics of an electromechanical and electrohydrostatic actuator are estimated with reasonably good accuracy with only four design parameters as input.